マクマード カザンガン ルイ ノ コチジキ - 船木, 實; フナキ, ミノル; Funaki, Minoru (1983)
P(論文) 合計212個の古地磁気学用試料を, マクマードサウンドのハットポイント半島, ロイズ岬, およびテイラー谷から採集した。これらの試料は安定な自然残留磁気を持つことが確かめられ, 以下に述べるような結果が得られた。(1)南極大陸は少なくとも鮮新世末期に, 現在の南極大陸の位置にあった。鮮新世末期から現代に至るまでの磁極の移動範囲は(正帯磁 : 11地点, 逆帯磁 : 3地点), 半径30°の南極域内で, その中心位置は, 現在の南極点の近くにあった。(2)この地域の溶岩の流出順序は, 古地磁気学, 地質学, それに年代学の結果を総合して, 新しいものから古い順に, 次のように推定される。ツインクレーターとロイズ岬(ブリュンス期), ハーフムーンクレーター(ハラミロ・イベント), オブザベーションヒルとアーミテージ岬(松山期), クレーターヒルとキャッスルロック(オルデュバイあるいはレユニオン・イベント), テイラー谷(カエナ・イベント)。 A total of 212 paleomagnetic samples were collected from the Hut Point Peninsula, the Cape Royds and the Taylor Valley in the McMurdo Sound, Antarctica. These samples have stable natural remanent magnetization. The results of paleomagnetic studies are as follows : (1) The position of Antarctica has been almost the same from the Late Pliocene Age up to the present. The position of the virtual geomagnetic pole (VGP) (11 normals and 3 reverses) from the Pliocene Age to the present is within a polar cap area of about 30°latitude, whose center is located almost exactly at the south geographical pole. (2) The sequence of lava eruption was determined by synthetic evidence from paleomagnetic, geological and geochronological data. The result revealed, from the latest to the earliest, Twin Crater Sequence and Cape Royds Sequence (Brunhes Epoch), Half Moon Crater Sequence (Jaramillo Event), Observation Hill Sequence, Cape Armitage Sequence (Matuyama Epoch), Crater Hill and Castle Rock (Olduvai or Reunion Events) and Taylor Valley Sequence (Kaena Event). departmental bulletin paper